2014
DOI: 10.1016/j.mspro.2014.07.124
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of Ni-P Coated Si 3 N 4 Reinforced Al6061 Composites

Abstract: Ni-P coated Si 3 N 4 reinforced Al6061 composites were fabricated by stir casting technique. Silicon nitride particles were varied in steps of 2 from 6 wt.% to 10 wt.%. Cast matrix alloy and developed composites were hot forged at a temperature of 500 • C using a 300T hydraulic hammer. Both as cast, hot forged matrix alloy and its composites were subjected to microstructural studies and fatigue strength tests. Microstructural studies reveal even distribution of silicon nitride particles with excellent bond bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…The Al 2 O 3 -SiC particulates may get crushed to powder form to maintain the wear resistance as detected in the results of wear rate [32,33]. Similar results have been noticed [5] and it is concluded that, from the analysis it is seen that, the SEM analysis of worn-out surfaces of the MMCs (Al7075 + 2%Al 2 O 3 + 3%SiC) is different from that of Al7075 + 5%Al 2 O 3 + 7%SiC composite. [34].…”
Section: Morphological Analysissupporting
confidence: 68%
“…The Al 2 O 3 -SiC particulates may get crushed to powder form to maintain the wear resistance as detected in the results of wear rate [32,33]. Similar results have been noticed [5] and it is concluded that, from the analysis it is seen that, the SEM analysis of worn-out surfaces of the MMCs (Al7075 + 2%Al 2 O 3 + 3%SiC) is different from that of Al7075 + 5%Al 2 O 3 + 7%SiC composite. [34].…”
Section: Morphological Analysissupporting
confidence: 68%
“…Here we see a potential for a significant increase in the specific modulus through small additions of Si 3 N 4 fibre. The tensile values demonstrated that the addition of hard Si 3 N 4 reinforcement increases the strength of the Alumix123 matrix through increased resistance to tensile stresses [22], with a minor reduction in ductility. The larger (than expected) variation in the tensile test results is due to the nature of the PM test specimens which are unmachined.…”
Section: Elastic Modulusmentioning
confidence: 96%
“…Si 3 N 4 is a low density (3.1 g/cm 3 ) ceramic material with high mechanical strength and hardness, good thermal and chemical stability, and good wear and corrosion resistance. It is of current interest as reinforcement in the manufacturing of MMCs [19][20][21][22]. Several works have been reported on fabrication and mechanical characterisation of aluminium matrix composite reinforced with Si 3 N 4 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum matrix composites when reinforced with hard ceramic particles replace monolithic materials and finds a wide range of application in automobile, transportation, defense and aerospace industries due to its improved properties such as high strength, improved wear resistance, high corrosion resistance, low density, heat treatment capability, high elastic modulus, high strength-to-weight ratio and high thermal conductivity [1][2][3][4]. Among the 7xxx series aluminum alloys, AA7068 is one of the most famous one which provides high strength and improved mechanical properties [5].…”
Section: Introductionmentioning
confidence: 99%